Optical properties of 2, 6-di(pyrazin-2-yl)pyridines substituted with extended aryl groups. (April 2021) - Małecka, Magdalena; Machura, Barbara; Szlapa-Kula, Agata
Abstract: A convenient one-pot method based on Kröhnke condensation was used to obtain a series of new 2, 6-di(pyrazin-2-yl)pyridines (dppy) functionalized with polyaromatic Ar groups: 1-naphthyl, 2-naphthyl, 9-anthryl, 9-phenanthryl, 1-pyrenyl and 2-triphenylenyl. From a structural point of view, the designed Ar-dppys are regarded as analogues of 2, 2′:6′, 2″-terpyridines, which are the most extensively used organic building blocks for supramolecular and coordination chemistry. The main emphasis of the current research was put on systematic studies of the impact of the extended aryl group on electrochemical, thermal and photophysical properties of Ar-dppys. The pendant aryl units in the studied Ar-dppys differ in the π-conjugation length, torsional hindrance due to the inter-ring H⋯ H repulsions and abilities for donation of electron density into π-conjugated trisheterocyclic unit (dppy). To get a deeper and wider understanding structure-property relationships, all presented Ar-dppys were also compared with previously reported aryl-substituted 2, 2′:6′, 2″-terpyridines (Ar-terpys). Additionally, the impact of solvent polarity on optical behavior of Ar-dppys was studied. Graphical abstract: Image 1 Highlights: Kröhnke condensation was used to obtain a series of 2, 6-di(pyrazin-2-yl)pyridines with pendant aryl groups. The impact of aryl substituents on optical and electrochemical properties of Ar-dppy was investigated. To get a wider structure-property relationships, Ar-dppys were discussed in relation to Ar-terpys . Contribution of ICT was evidenced experimentally for 1-pyrenyl-substituted dppy.